Language assessment in Mexico: Exploring university language teachers' backgrounds, practices, and opinions. (November 2022) - Banitz, Brita
Abstract: Assessment is a vital aspect of any language teaching program and yet, no uniform assessment criteria exist in Mexico. To explore the role of language assessment in higher education in the country, a study employing a mixed-method approach was conducted. The data discussed in this article are based on a survey of university language teachers in Mexico investigating their educational backgrounds, their language assessment practices, and their opinions towards language assessment. Interviews with language teachers and program coordinators provided further insight into the university language teachers' experiences and concerns regarding language assessment in the country. The article also includes an overview of Mexico's particular educational context as it contributes to the overall dissatisfaction with the outcomes of language instruction. Since the results of the study indicate that the majority of language teachers in Mexico are part-time professors operating without clear guidelines and many of them feel somewhat insecure about language assessment, it is suggested that specific language assessment competencies be formulated for these teachers which should be met in future teacher training programs. Assessing the students' language learning outcomes at the individual program level is subsequently proposed as a concrete measure to improve the language education outcomes in Mexico.